The conservation works of heritage mosques in Kelantan / Azura Rossalina Mohamad Zaidi and Mohd Farid Sa'ad - Mohamad Zaidi, Azura Rossalina; Sa'ad, Mohd Farid (2018)
The heritage mosque is one of the contributors to diversity of architectural design in Malaysia. The heritage building can portray the diversity of cultural property which conserves and maintains the continuity of vernacular architecture and history of the country. In Malaysia, conservation of heritage buildings is initiated by the government and public sector. The establishment of the National Heritage Department of Malaysia in 2006 shows that the government wants to appreciate the existence of heritage buildings in Malaysia. This paper will focus on the conservation works on heritage mosques located in Kota Bharu, Kelantan. In order to achieve the aims, two objectives have been chosen which are to determine the building elements of heritage mosques in Kota Bharu, Kelantan; and to analyse the success rates of building elements towards conservation works on heritage mosques in Kota Bharu, Kelantan.To make sure this research is reliable, an elemental observation was carried out to analyse success rates of conservation works on Kampung Laut Mosque and Masjid Lama Mulong. Besides that, formal and informal interviews were conducted to know the history of mosques and the defects present during preservation. The data obtained was analysed by using Microsoft Excel and the reults presented in the form of bar charts. This research is carried out to do improvement of conservation works by following conservation principle. The heritage building remains as one of the important cultural value that able inherent to the afterward generations.